Identification of potential risk factors associated with highly pathogenic avian influenza subtype H5N1 outbreak occurrence in Lagos and Kano states, Nigeria, during the 2006-2007 epidemics - Métras, Raphaëlle; Stevens, K.B.; Abdu, P.; Okike, Iheanacho; Randolph, Thomas F.; Grace, Delia; Pfeiffer, Dirk U.; Costard, Solenne (Hindawi Limited, 2013)
Highly pathogenic avian influenza HPAI H5N1 was first reported in Africa in 2006, in Nigeria. The country experienced severe outbreaks in 2006 and 2007, strongly affecting the poultry population. Current knowledge on potential risk factors for HPAI H5N1 occurrence in poultry farms in Nigeria is limited. Therefore, we conducted a case–control study to identify potential farm-level risk factors for HPAI H5N1 occurrence in two areas of the country that were affected by the disease in 2006 and 2007, namely the States of Lagos and Kano. A case–control study was conducted at the farm level. A convenience sample of 110 farms was surveyed. Data on farm characteristics, farm management and trade practices were collected. Logistic regression was used to identify factors associated with farms that confirmed positive for HPAI. Having a neighbouring poultry farm was identified as a potential risk factor for disease occurrence [OR, 5.23; 95% CI, (0.88–30.97); P-value = 0.048]. Farm staff washing their hands before handling birds was a protective factor [OR, 0.14; 95% CI, (0.05–0.37); P-value <0.001], as well as not allowing traders to enter the farm [OR, 0.23; 95% CI, (0.08–0.70); P-value = 0.008]. Our study highlighted the importance of trade and proximity between poultry farms in the epidemiology of HPAI H5N1 and the role of biosecurity in disease prevention in Kano and Lagos States. Despite the limitations owing to the sampling strategy, these results are consistent with other risk factor studies previously conducted on HPAI H5N1 in both Africa and other regions, suggesting similar risk factor patterns for HPAI H5N1 virus spread and substantiating current knowledge regarding the epidemiology of the disease. Finally, this study generated information from areas where data are difficult to obtain.